A bone-resorption surface-targeting nanoparticle to deliver anti-miR214 for osteoporosis therapy - Cai M (Dove Medical Press, 2017)
Mingxiang Cai,1,* Li Yang,2,* Shufan Zhang,1 Jiafan Liu,2 Yao Sun,1 Xiaogang Wang2 1Engineering Research Center of Tooth Restoration and Regeneration, Department of Oral Implantology, School of Stomatology, Tongji University, Shanghai, 2Department of Cell Biology, Institute of Biomedicine, College of Life Science and Technology, Jinan University, Guangzhou, China*These authors contributed equally to this work Abstract: With increasing fracture risks due to fragility, osteoporosis is a global health problem threatening postmenopausal women. In these patients, osteoclasts play leading roles in bone loss and fracture. How to inhibit osteoclast activity is the key issue for osteoporosis treatment. In recent years, miRNA-based gene therapy through gene regulation has been considered a potential therapeutic method. However, in light of the side effects, the use of therapeutic miRNAs in osteoporosis treatment is still limited by the lack of tissue/cell-specific delivery systems. Here, we developed polyurethane (PU) nanomicelles modified by the acidic peptide Asp8. Our data showed that without overt toxicity or eliciting an immune response, this delivery system encapsulated and selectively deliver miRNAs to OSCAR+ osteoclasts at bone-resorption surface in vivo. With the Asp8-PU delivery system, anti-miR214 was delivered to osteoclasts, and bone microarchitecture and bone mass were improved in ovariectomized osteoporosis mice. Therefore, Asp8-PU could be a useful bone-resorption surface-targeting delivery system for treatment of osteoclast-induced bone diseases and aging-related osteoporosis. Keywords: osteoporosis, microRNA, bone resorption, targeting delivery, nanoparticle